PERMAINAN TRADISIONAL MADURA: DARI PERMAINAN TANJAN KE IDE AKTIVITAS SPATIAL SKILLS DALAM PEMBELAJARAN MATEMATIKA - R. A. Qothrun Nada Syauqina; Indah Setyo Wardhani; Noril Lailatul Chusna; Sukriya Ulfa; Izza Fijriyah (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The tanjan game is believed to be one of the cultural games in Madura. In addition to being an enjoyable game, this game also requires spatial skills, as players are able to engage with spatial images directly. This research employs a qualitative approach, with the researcher as a participant. Data were collected through observation, documentation, and a literature review on spatial skills components. The data analysis techniques used are data reduction, data display, and verification. This study has identified eleven spatial skill activities from the traditional tanjan game. These activities are in line with the spatial skill components, starting from before the game starts or when drawing tanjan to when the tanjan game takes place. In addition, this study determines the mathematical elements contained in each spatial skill activity.